Strategi E-Marketing Destinasi Wisata Sebagai Daya Untuk Meningkatkan Kunjungan Pasca Pandemi - Utomo, Danang Prio; Pahrudin, Pahrudin; Sari, Lidya Maya (Universitas Hamzanwadi, 2023)
The purpose of this study was to determine e-marketing strategies for tourist destinations in East Lombok, especially the Sembalun tourist attraction. The research method used is qualitative research using primary data obtained through observation and interviews. Data analysis using SWOT analysis. The results of the study show that there are several weaknesses in Sembalun tourism, namely that e-marketing is not maximized because the majority of management is still personal. Strengthening e-marketing needs to be improved where this tour has a good opportunity to be visited by tourists again through digital promotional activities. Strengthening this e-marketing strategy can be done by training human resources who are actors in the tourism sector so that they can utilize social media and online platforms in creating promotional content to expand the reach of promotions to people in various regions. Promotions carried out on social media are the most effective alternative to implement because of the speed and ease of delivering information. It can be concluded from this research that in increasing tourist visits, the e-marketing strategy is an appropriate alternative to be implemented and understood by Sembalun tourism managers.